Effect of the North Atlantic Oscillation on Ice Phenomena on Selected Lakes in Poland Over the Years 1961–2010 - Wrzesiński, Dariusz; Ptak, Mariusz; Baczyńska, Alicja (Quaestiones Geographicae, 2013)
An analysis is presented of changes in the parameters of ice phenomena on selected Polish lakes over the years 1961-2010 against the background of variations in the intensity of the North Atlantic Oscillation. The following features were analysed: the start and end of ice phenomena and ice cover, their duration, and the stability of ice cover at observation sites of the Institute of Meteorology and Water Management on lakes located in various physical-geographic regions. Multi-year tendencies of change in the ice parameters under study were identified. The most statistically significant negative trends were observed for the ending dates of ice phenomena and their duration. Changes in the ice characteristics in the different NAODJFM stages were determined on the basis of their deviations: between years with high (> 1.7) and low (< -1.09) values of the winter NAO index, and from average values from the years 1961-2010. Changes in the intensity of the North Atlantic Oscillation affect all the parameters of ice phenomena except their starting dates. In a negative NAODJFM stage, ice phenomena and ice cover end later and last longer; also, the maximum thickness of ice cover is greater, its forms later and is more stable than in a positive stage and in average conditions